2005
DOI: 10.1093/toxsci/kfi197
|View full text |Cite
|
Sign up to set email alerts
|

Protein Adduct Formation as a Molecular Mechanism in Neurotoxicity

Abstract: Chemicals that cause nerve injury and neurological deficits are a structurally diverse group. For the majority, the corresponding molecular mechanisms of neurotoxicity are poorly understood. Many toxicants (e.g., hepatotoxicants) of other organ systems and/or their oxidative metabolites have been identified as electrophiles and will react with cellular proteins by covalently binding nucleophilic amino acid residues. Cellular toxicity occurs when adduct formation disrupts protein structure and/or function, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(134 citation statements)
references
References 115 publications
4
129
0
1
Order By: Relevance
“…Sirt 1 is closely involved in with chromatin modification and protection of neurons from genotoxic stress with the involvement of DNA repair enzymes and repair of double strand breaks in damaged chromatin structure [131,132]. In liver and brain cells with low Sirt 1 activity electrophiles from xenobiotic metabolism react with micro ribonucleic acid (RNA) [133][134][135] or by covalent binding to nucleophillic centres in cellular protein and DNA [136][137][138][139]. Adduct formation disrupts DNA or protein structure with damage to the nucleus and various subcellular organelles [128,130,140] such as the ER and mitochondria with metabolic alterations.…”
Section: Metabolic Disorders Affect the Metabolism Of Xenobiotics Andmentioning
confidence: 99%
“…Sirt 1 is closely involved in with chromatin modification and protection of neurons from genotoxic stress with the involvement of DNA repair enzymes and repair of double strand breaks in damaged chromatin structure [131,132]. In liver and brain cells with low Sirt 1 activity electrophiles from xenobiotic metabolism react with micro ribonucleic acid (RNA) [133][134][135] or by covalent binding to nucleophillic centres in cellular protein and DNA [136][137][138][139]. Adduct formation disrupts DNA or protein structure with damage to the nucleus and various subcellular organelles [128,130,140] such as the ER and mitochondria with metabolic alterations.…”
Section: Metabolic Disorders Affect the Metabolism Of Xenobiotics Andmentioning
confidence: 99%
“…The neurotoxic effects of HEX are related to 2,5-HD 11,15) , an active γ -diketone that is the only neurotoxic metabolite of HEX. Recent studies have shown that axon atrophy is the morphological hallmark of γ -diketone neuropathy 16,17) and that regardless of exposure rate (100−400 mg/kg/day), it is an early consequence of 2,5-HD neurotoxicity and a necessary event in the pathophysiological process that leads to γ -diketone neurological toxicity 18) . Use of the urinary concentration of free 2,5-HD has been proposed for biological monitoring of workers exposed to HEX 19−23) , and the American Conference of Governmental Industrial Hygienists (ACGIH) proposed a value of 0.4 mg/l as the reference value for it 20) .…”
Section: Abstract : a S Y M P T O M A T I C S H O E M A K E R S mentioning
confidence: 99%
“…The epoxide group of GA makes it more electrophilic than AA and can bind with DNA. GA-DNA adducts have been isolated in animal studies and is proposed to be the compound responsible for the genotoxicity of AA [13,14]. Studies have shown that AA will preferentially bind with proteins, free amino acids, and thiols, than with DNA [12,13].…”
Section: Introductionmentioning
confidence: 99%